Extruded-expelled cottonseed meal (Express) as a source of protein and fat for lactating dairy cows - A.F. Park; M.V. Sheffel; Evan C. Titgemeyer; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1998)
Twenty-four Holstein cows were used in six 4x4 Latin squares to evaluate the effects of substituting extruded-expelled cottonseed meal (Express™) for whole cottonseed and solvent soybean meal in diets for lactating cows. No differences were observed in milk and milk component yield among treatments. Percentages of fat, protein, solids-not-fat, and lactose in milk were similar among treatments. Replacing whole cottonseed with Express™ tended to reduce milk urea nitrogen but had no effect on milk protein percentage or yield. Cow acceptability of Express™ was excellent throughout the 84-day study conducted between late June and September when ambient temperature exceeded 100EF for 35 days. Long-term storage of Express™ in a commodity barn was not a problem. In vitro analysis of Express™ revealed that it contains approximately 75% rumen undegradable protein (RUP) with an intestinally absorbable dietary protein value of 53.4%. Express™ is an excellent source of RUP, and the protein fraction is highly digestible in the small intestine.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Lactating cows; Extruder-expelled cottenseed meal